2017
DOI: 10.1080/09712119.2017.1394860
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single radial immunodiffusion and ELISA for the quantification of immunoglobulin G in bovine colostrum, milk and calf sera

Abstract: The overall objective was to compare immunoglobulin G (IgG) concentrations measured by single radial immunodiffusion (sRID) and ELISA-based methods in samples of bovine colostrum and transition milk from contrasting breed types (Limousin × Friesian (n = 10) and Holstein (n = 10)). Jugular blood samples were collected at 48 h post-birth from beef (n = 10) and dairy (n = 10) calves and sera harvested subsequent to colostrum consumption. Absolute colostrum IgG values determined by ELISA showed poor agreement with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
51
2
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 38 publications
4
51
2
9
Order By: Relevance
“…The correlation between % Brix and IgG determined by sandwich ELISA in our study was also lower (device 1: r = 0.50; device 2: r = 0.55) than in other studies (Morrill et al, 2013;Deelen et al, 2014;Elsohaby et al, 2015;Hernandez et al, 2016;Cuttance et al, 2017). Two recent studies evaluated the agreement between an ELISA and RID to analyze IgG in serum of calves and found only weak to moderate correlations (Gelsinger et al, 2015;Dunn et al, 2018). According to Gelsinger et al (2015), the concentration of IgG was significantly lower in serum and colostrum samples when measured by ELISA compared with RID, and their study results indicated that the RID is a more consistent method.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…The correlation between % Brix and IgG determined by sandwich ELISA in our study was also lower (device 1: r = 0.50; device 2: r = 0.55) than in other studies (Morrill et al, 2013;Deelen et al, 2014;Elsohaby et al, 2015;Hernandez et al, 2016;Cuttance et al, 2017). Two recent studies evaluated the agreement between an ELISA and RID to analyze IgG in serum of calves and found only weak to moderate correlations (Gelsinger et al, 2015;Dunn et al, 2018). According to Gelsinger et al (2015), the concentration of IgG was significantly lower in serum and colostrum samples when measured by ELISA compared with RID, and their study results indicated that the RID is a more consistent method.…”
Section: Discussioncontrasting
confidence: 78%
“…The size of the ring depends on the amount of antigen contained in the solution applied. The diameters of the precipitate rings were measured using a magnifying loupe and were plotted against the IgG concentrations of the standards using linear regression (Dunn et al, 2018). Disadvantages are a low antigen concentration that reduces accuracy and an uneven spread that can confound results.…”
Section: Discussionmentioning
confidence: 99%
“…In our study there was only a weak correlation between sandwich ELISA and Brix refractometry (r = 0.44). Obviously, results obtained by sandwich ELISA and RID cannot be directly compared (Dunn et al, 2017). Therefore, the results in our study generated by sandwich ELISA limits the comparability with other studies using RID.…”
mentioning
confidence: 59%
“…Для определения иммунобиологической полноценности молозива коров, связанной с содержанием в нем иммуноглобулинов, применяются как физические (по удельной плотности), так и иммунологические методы оценки: радиальная иммунодиффузия (РИД) -«золотой стандарт», различные варианты иммуноферментного анализа (ИФА), а также в качестве экспресс-метода может рассматриваться реакция латекс-агглютинации (РЛА). Эти тесты направлены на определение уровня IgG -основного изотипа иммуноглобулинов в молозиве, обладающего выраженными защитными функциями [3,8].…”
Section: The Problem Of Preservation Of Newborn Calves In the Early Punclassified
“…Определение активности гамма-глютамилтрансферазы в сыворотке крови для оценки пассивной передачи иммунитета (фермент продуцируется клетками молочной железы, и его выявление в сыворотке крови телят рассматривается как результат получения молозива) имеет неоднозначные результаты и практически не используется для этих целей. Период времени после рождения, когда этот тест может быть использован, составляет 8-10 дней [3,8].…”
Section: The Problem Of Preservation Of Newborn Calves In the Early Punclassified